Antenatal and delivery services in Kinshasa, Democratic Republic of Congo: care‐seeking and experiences reported by women in a household‐based survey. Issue 10 (22nd August 2013) - Feinstein, Lydia; Dimomfu, Bruno Lapika; Mupenda, Bavon; Duvall, Sandra; Chalachala, Jean Lambert; Edmonds, Andrew; Behets, Frieda
Abstract: Objectives: Increasing coverage of quality reproductive health services, including prevention of mother‐to‐child transmission services, requires understanding where and how these services are provided. To inform scale‐up, we conducted a population‐based survey in Kinshasa, Democratic Republic of Congo. Methods: Stratified two‐stage cluster sampling was used to select women ≥18 years old who had been pregnant within the prior three years. Participants were interviewed about their reproductive healthcare utilization and impressions of services received. Results: We interviewed 1221 women, 98% of whom sought antenatal care (ANC). 78% of women began ANC after the first trimester and 22% reported <4 visits. Reasons for choosing an ANC facility included reputation (51%), friendly/accessible staff (39%), availability of comprehensive services (29%), medication access (26%), location (26%), and cost (21%). Most women reported satisfactory treatment by staff, but 47% reported that the ANC provider ignored their complaints, 23% had difficulty understanding responses to their questions, 22% wanted more time with the provider, 21% wanted more privacy, and 12% felt uncomfortable asking questions. Only 56% reported someone talked to them about HIV/AIDS. Strongest predictors of seeking inadequate ANC included low participant and partner education and lack of certain assets. Only 32% of women sought postnatal care. Some results varied by health zone. Conclusions: Scaling‐up interventions to improve reproductive health services should include broad‐based health systems strengthening and promote equitable access to quality ANC, delivery, and postnatal services. Personal and structural‐level barriers to seeking ANC need to be addressed, with consideration given to local contexts.